The Effect of the Reciprocal Teaching Model on Students' Critical Thinking Skills in Grade IV Natural and Social Sciences (IPAS) Learning at SD Negeri 4 Padoang-Doangan - Kamaruddin H; Nurul Mukhlisa; Oggia Pinasti (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Students’ critical thinking skills in Natural and Social Sciences (IPAS) remain underdeveloped because teacher-centered instruction provides limited opportunities to analyze information, articulate arguments, and formulate conclusions. This study aimed to compare the critical thinking skills of fourth-grade students taught through the Reciprocal Teaching model with those taught through conventional instruction and to determine the effect of the model on students’ critical thinking performance at SD Negeri 4 Padoang-Doangan. A quantitative quasi-experimental approach with a pretest–posttest control group design was employed. The sample comprised 46 students, including 22 students in the experimental group and 24 students in the control group. Data were collected using a critical thinking skills test and analyzed through descriptive and inferential statistics using SPSS Statistics version 26. The findings showed that the experimental group achieved a higher mean posttest score than the control group (86.14 vs. 77.29). The N-Gain analysis classified 14 experimental-group students in the high category and 8 in the moderate category, whereas the control group comprised 2 students in the high category, 21 in the moderate category, and 1 in the low category. The independent-samples t test yielded p < .001, indicating a statistically significant difference between the two groups. These findings demonstrate that Reciprocal Teaching significantly enhances students’ critical thinking skills in fourth-grade IPAS learning. The study contributes practical evidence that structured activities involving questioning, clarifying, summarizing, and predicting can provide a more participatory instructional alternative for developing elementary students’ analytical reasoning and conclusion-formulation skills.